(untitled) (Journal of the College of Basic Education, 2022)
This research describes the development of a new microelectrode sensor (MES) for in situ measurements of dissolved oxygen (DO) using microfabrication technologies. A dynamic etching technique was used to fabricate 20 mm long sensor probes and sharpen them to micrometer dimensions. The sensors utilized a gold sensing electrode inside a recess fabricated at the tip of each microelectrode. Electrochemical performance of these (dissolved oxygen MES) sensors was fully characterized by measuring the oxygen concentration of saline solutions with a Ag/AgCl reference electrode. The DO MES exhibited a rapid 30 seconds linear response in the 0–9 mg/L range. The (dissolved oxygen MES) microelectrode sensor was successfully applied to evaluation of DO microproﬁles in a multi-species aerobic bacterial ﬁlm. The developed new sensors are able to measuring DO in situ analysis in many biological applications.